Usulan Standar Tingkat Pencapaian Perkembangan Anak (STPPA) Pendidikan Anak Usia Dini Usia 2-3 Tahun - Nor Annisa; Nanik Rahayu; Noor Padilah; Saniyya Putri Hendrayana; Reni Rulita; Debie Susanti (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
This article discusses the process of growth and development of children aged 2-3 years which is continuous throughout the stages of life, but the speed of growth varies according to the stages of age. In the development of children aged 2-3 years. To achieve development, children need to achieve it in accordance with the standards of the child's level of achievement: religious-moral, physical-motoric, cognitive, linguistic, social-emotional, and artistic, language and art. This article aims to describe the development of abilities of children aged 2-3 years from various aspects of developmental achievement. Development is the increase in abilities   or   skills   in   more   complex   body   structures   and functions in a regular and predictable pattern as a result of experience and the process of movement, intellectual, social and emotional maturation.  Development is influenced by heredity, environment, culture and family values in each individual. The combination of these factors gives rise to the wide variety of variations that can be observed in children. Growth   and   development   occur   very   rapidly, therefore stimulation of children at this age is very important because healthy   and   intelligent   children   will   grow   and   develop optimally.  The rate of growth and development of children aged 2-3 years which is described in various sources and guidelines in the national curriculum, there are proposed indicators of development in aspects of religious-moral, physical-motoric, cognitive, linguistic, social-emotional, and artistic. The method used for data collection is in the form of library research, which is a method that can study various reference books and the results of previous similar studies.